FLUORESCEIN ANGIOGRAPHY FINDINGS IN UNILATERAL PERSISTENT FETAL VASCULATURE. Issue 3 (March 2020) - Shen, Jen-Hsiang; Liu, Laura; Wang, Nan-Kai; Hwang, Yih-Shiou; Chen, Kuan-Jen; Chao, An-Ning; Lai, Chi-Chun; Chen, Tun-Lu; Wu, Wei-Chi
Abstract : Objective: This study aims to examine retinal vascular findings for affected eyes and contralateral eyes as well in typical cases of unilateral persistent fetal vasculature. Methods: We retrospectively reviewed all patients evaluated at Chang Gung Memorial Hospital, Linkou, for unilateral persistent fetal vasculature between January 2008 and July 2017. All patients underwent fluorescein angiography (FA) examination under general anesthesia. FA was performed using RetCam 3 (Clarity Medical Systems, Inc, Pleasanton, CA). Results: Ten patients (eight male and two female) were identified as having adequate clinical data for the final analysis. The mean age at diagnosis was 13.7 ± 17.2 months (range 1–58). The mean axial length was shorter in the affected eyes as compared to the fellow eyes (17.27 ± 2.8 vs. 20.2 ± 1.7 mm; P = 0.024). In the affected eyes, nine cases (90.0%) showed a concomitant retrolental stalk, avascular peripheral retina, regional capillary dropout, and absence of foveal avascular zone. Hyperfluorescent stalk was seen in seven cases (70.0%). Four eyes (40.0%) showed leaking vessels. Terminal supernumerary branching was seen in two cases (20.0%). Popcorn hyperfluorescence was noted in one case (10.0%). In the fellow eyes, peripheral avascular zone was noted in nine eyes (90.0%), of which six (60.0%) had peripheral zones greater than two-disk diameters. Seven eyes (70.0%) presented with regional capillary dropout and abnormal choroidal filling. Three eyes (30.0%) had abnormal vessel straightening. Aberrant circumferential vessels and leaking spots were seen in two eyes (20.0%). Regional dilation of disk vessels, peripheral vessel dilation, and terminal bulbing were noted in one eye (10.0%). The mean best-corrected visual acuity of the fellow eyes was 20/39 (0.29 in logarithm of the minimum angle of resolution). Conclusion: Retinal vascular abnormalities in the affected eyes and fundoscopically normal fellow eyes of unilateral persistent fetal vasculature patients were found in 100% and 90.0% of patients, respectively. Fellow eyes had some subtle abnormalities that were only revealed through FA. These unilateral persistent fetal vasculature cases were still bilaterally affected. Abstract : Retinal vascular abnormalities in the affected eyes and fellow eyes of unilateral persistent fetal vasculature were found in 100% and 90.0% of patients, respectively, revealed through FA. These unilateral persistent fetal vasculature cases were still bilaterally affected.